Amplification of 16S rRNA gene sequences to differentiate two highly related bradyrhizobia species - Giongo, Adriana; Ambrosini, Adriana; Freire, João Ruy Jardim; Zanettini, Maria Helena Bodanese; Passaglia, Luciane Maria Pereira (Pesquisa Agropecuaria Brasileira, 2007)
A 16S rRNA gene PCR-based assay was developed aiming at a fast molecular diagnostic method to differentiate the two phylogenetically closely related species Bradyrhizobium japonicum and B. elkanii, isolated from soybean nodules, in order to identify those more competitive and comprising greater nitrogen fixation ability for use in the formulation of commercial inoculants. The assay used was able to discriminate ten reference strains belonging to these two Bradyrhizobium species, as well as to efficiently identify 37 strains isolated from fields cultivated with soybean.